2019
DOI: 10.1002/btpr.2862
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the combination of single‐pass tangential flow filtration and anion exchange chromatography for intensified mAb polishing

Abstract: There is growing interest within the biopharmaceutical industry to improve manufacturing efficiency through process intensification, with the goal of generating more product in less time with smaller equipment. In monoclonal antibody (mAb) purification, a unit operation that can benefit from intensification is anion exchange (AEX) polishing chromatography. Single‐pass tangential flow filtration (SPTFF) technology offers an opportunity for process intensification by reducing intermediate pool volumes and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…The viral clearance performance of AEX is influenced by many variables, including the pH and conductivity of the feed and process buffer solutions, load density, flow rate and residence time, all of which have been widely explored in many studies (Miesegaes et al, 2014; Roush, 2014; Strauss et al, 2010; Strauss, Gorrell, et al, 2009; Strauss, Lute, et al, 2009). Eshmuno Q has been shown to achieve consistent levels of viral clearance for MMV (LRV > 5) under the pH (7.5–8.5), conductivity (up to 6 mS/cm), resin load (up to 250 g/L), and residence time (2–8 min) used in this study, and this was confirmed using spiking/loading Method 1 (Elich, Goodrich, Lutz, & Mehta, 2019; Mehta et al, 2016). The current study focused on the impact of potential fluctuations in load and viral spike concentrations that might be introduced by connected, continuous processes, on the viral clearance performance of AEX in flow‐through mode.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The viral clearance performance of AEX is influenced by many variables, including the pH and conductivity of the feed and process buffer solutions, load density, flow rate and residence time, all of which have been widely explored in many studies (Miesegaes et al, 2014; Roush, 2014; Strauss et al, 2010; Strauss, Gorrell, et al, 2009; Strauss, Lute, et al, 2009). Eshmuno Q has been shown to achieve consistent levels of viral clearance for MMV (LRV > 5) under the pH (7.5–8.5), conductivity (up to 6 mS/cm), resin load (up to 250 g/L), and residence time (2–8 min) used in this study, and this was confirmed using spiking/loading Method 1 (Elich, Goodrich, Lutz, & Mehta, 2019; Mehta et al, 2016). The current study focused on the impact of potential fluctuations in load and viral spike concentrations that might be introduced by connected, continuous processes, on the viral clearance performance of AEX in flow‐through mode.…”
Section: Resultssupporting
confidence: 68%
“…Each bar represents the mean of two runs. MMV, mouse minute virus; TCID50, 50% tissue culture infectious dose [Color figure can be viewed at wileyonlinelibrary.com] to achieve consistent levels of viral clearance for MMV (LRV > 5) under the pH (7.5-8.5), conductivity (up to 6 mS/cm), resin load (up to 250 g/L), and residence time (2-8 min) used in this study, and this was confirmed using spiking/loading Method 1 (Elich, Goodrich, Lutz, & Mehta, 2019;Mehta et al, 2016). The current study focused on the impact of potential fluctuations in load and viral spike concentrations that might be introduced by connected, continuous processes, on the viral clearance performance of AEX in flow-through mode.…”
Section: Viral and Hcp Clearance By Different Load And Spike Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…Apart from these steps, viral inactivation is also used for recombinant biopharmaceuticals produced using mammalian cells (Zydney, 2016). Cell disruption is required for recovery of the desired proteins, expressed as intracellular IBs (Ehgartner et al, 2017). The commonly used cell disruption methods at large scale include high-pressure homogenizers and bead mills (Mevada et al, 2019).…”
Section: Downstream Process Developmentmentioning
confidence: 99%
“…Single-pass tangential flow filtration can be used to concentrate process intermediates, resulting in potential advantages such as smaller intermediate hold tanks and reduced loading times for subsequent unit operations. 7 These smaller volume, higher concentration intermediates have reduced water and buffer requirements for dilution to achieve compatibility with conditions for downstream purification operations. For polishing chromatography, the mass loading and efficiency of impurity removal is increased due to the higher binding capacity for impurities such as host cell proteins at higher protein concentrations.…”
mentioning
confidence: 99%